Towards responsive architecture: an exploration of massing in design process / Zalina Samadi, Nurul Husna Qamaruzzaman and Firdaus Al-Siddiq Fadzil - Samadi, Zalina; Qamaruzzaman, Nurul Husna; Fadzil, Firdaus Al-Siddiq (2010)
Massing study is part of the space organization in design process. The space organization in the study manifests the basic space relationship with the immediate surroundings context. The paper covers the explorative research in the design-based architectural education (DBAE), content analysis and observational analysis as methodology of the research. The aim of the research was to investigate the level of awareness and massing typology amongst architecture students towards responsive architecture. The awareness level among students could be presumed as a reflection of Malaysian architectural education towards the materialization of sustainable issues in Agenda 21. The inclusion of the paper offers an exploration of built-form massing in the architectural education in Universiti Teknologi MARA. The findings unfolded in this paper could establish the relationship between awareness level and built-form massing in the design process had influenced the design features. With that, in the future designers shall consider the passive-design approach in design process and not after-thought treatment.